The Challenge of Implementing Cambridge Curriculum in Elementary School - Muamaroh; Hastuti, Diyah Murti; Muzaedah (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
English language teaching in elementary schools has become a popular issue due to the decision of the Minister of Education that English will be a compulsory subject for elementary schools. Some elementary schools have used the Cambridge curriculum which is quite challenging for teachers to teach in English classes. This study aims to analyze the challenges of implementing the Cambridge curriculum in teaching English to elementary school students with a case study approach. The subjects of this study were two English teachers. The method in this study used descriptive qualitative research using a case study research design. Data collection used was observation and interviews which were analyzed qualitatively through content analysis. The results of the study showed that the challenges faced by teachers in implementing the Cambridge curriculum were that teachers needed more preparation time to start learning; students easily lost concentration during learning; students had different learning styles and they felt insecure to practice speaking English. To overcome these problems, teachers used variations and tones of voice and direct instructions to start lessons; they also used various types of teaching techniques such as songs, watching videos and games. In addition, teachers also use two languages, namely Indonesian and English in the learning process to make it easier for students to understand the lessons, as well as train students to increase their confidence in speaking English.